ENSO Impacts on Lomas Formation in South Coastal Peru: Implications for the Pliocene? - Timothy Paul Eichler; Ana C. Londoño (Advances in Meteorology)
Lomas formations in southern Peru are related to moisture availability due to frequent incursions of fog in austral winter. Due to warming of coastal waters of southern Peru during El Niño, lomas formations are enhanced via greater moisture availability for fog and drizzle. Our study evaluates the modern climatological record in austral winter to determine if there are differences in moisture availability between El Niño and La Niña for fog formation. Our results show anomalous northwesterly onshore flow, warmer than normal sea-surface temperatures, and an increase in precipitable water in El Niño, favoring lomas formations due to advection fog with higher moisture content. On the other hand, La Niña also favors frequent advection fog, with less moisture content due to strong onshore flow over relatively cool SSTs. Since lomas may represent fragments of a continuous vegetation belt that existed during the Pliocene, a permanent El Niño favoring vigorous vegetation production along the south Peruvian coast due to incursions of fog with high precipitable water may have occurred in this period. However, the possibility of normal El Niño variability superimposed on a warmer climatology producing fog with higher moisture content in both El Niño and La Niña conditions cannot be discounted.